UU Khusus LPP: Solusi Transformasi RRI-TVRI - Mr Masduki (Jurnal Komunikasi, 2013)
According to Broadcasting Law Number 32 Year 2002, Radio Republik Indonesia (RRI) and Televisi Republik Indonesia (TVRI) have become independent public services broadcasting institutions. Until 2012, the transformation of both still faces some obstacles, internally and externally. Both are still encountering identity crisis whether representing public or authority due to strong influence of power—not fully free from government intervention, problem of civil servants professionalism, and budget nomenclature. There is the need for a new and special law of public broadcasting in order to ensure protection and transformation of RRI and TVRI as public service broadcasting in the future.